Penurunan Pondasi Telapak Yang Diperkuat Kolom Kapur - Amsri, Rakhmatullah, Anto Budi Listyawan, S.T., M.Sc (2017)
Soil Strengthening is an attempt to increase the soil bearing capacity. An effort is needed to increase the soil bearing capacity. Vertical drain with lime column that used in footing foundation becomes a solution to increase the bearing capacity of the soil. The study presents six tests laboratory without lime column and with lime column which has circle shape diameter 100 mm, 150 mm and foundation diameter 100 mm, 150 mm and height 35 cm on clay homogen soil by maintaining water content and compaction method. The results from all laboratory tests is that the bigger diameter size of lime column and foundation diameter, increases the bearing capacity of soil. From laboratory test, we can conclude that by increasing the diameter of lime column and diameter of the foundation could increase the bearing capacity value. By increasing diameter of the foundation, make it has a higher bearing capacity than increasing the diameter of lime column. The bearing capacity's value of the soil that using lime column is higher than the bearing capacity without lime column. The highest settlement happen at the loading center, the closer loading distance to loading center, the higher value of settlement. Keywords: bearing capacity, lime column, loading test, settlement, footing foundation, homogen soil, vertical drain.